Screening and Identification of Herbal Urease Inhibitors Using Surface Plasmon Resonance Biosensor - Mahmood Biglar; Hafezeh Salehabadi; Safoura Jabbari; Bahareh Dabirmanesh; Khosro Khajeh; Faraz Mojab; Massoud Amanlou* (Iranian Society of Pharmacognosy, 2021)
Background and objectives: Urease, that catalyzes the hydrolysis of urea, has received substantial attention for its impact on living organisms' health and human life quality. Urease inhibitors play important role in management of different diseases including gastritis and other gastrointestinal disorders. In the present study, a new surface plasmon resonance-based biosensor was designed to discover new urease inhibitors. Methods: The biosensor surface was prepared by the covalent immobilization of urease on carboxymethyldextran hydrogel (CMD 500D) via its primary amine groups. Results: The biosensor combined with an orthogonal enzyme inhibition assay was utilized for screening of 40 traditional medicinal plant extracts against Jack-bean urease. Among them, Laurus nobilis leaf extract displayed a high affinity with the immobilized urease; therefore, its active compound (quercetin) was isolated and identified as a urease inhibitor. The equilibrium constant (KD) and Gibbs free energy (ΔGbinding) values for the interaction of quercetin with urease were obtained to be 55 nM and -41.62 kJ/mol, respectively. The results of molecular docking analysis also confirmed our findings. Conclusion: This SPR-based biosensor represents a new, fast, reliable, and an accurate technique for the identification of new urease inhibitors or novel 'lead' compounds from natural resources.